BIMBINGAN TEKNIS PEMBENIHAN IKAN KOMET (Carassius auratus) SEBAGAI PELUANG USAHA BARU BAGI ANGGOTA KELOMPOK TANI ‘BERSAMA’ DESA PADANG LUAS KECAMATAN KURAU KABUPATEN TANAH LAUT - Rini Marlida; Yulius Kisworo (INSPIRASI: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Comet fish (Carassius auratus) is a popular ornamental fish because it has beautiful colors and a beautiful tail shape. Cultivating ornamental fish can be a new business opportunity for members of the "BERSAMA" farmer group. Cultivating comet ornamental fish is very simple and easy so it can be done by beginners. One of the chains in the fish cultivation process is hatchery. The aim of P2M is to provide technical guidance regarding comet fish hatchery so that the knowledge gained by partners becomes a new business opportunity to increase income for members. There are 15 members of the farmer group involved in this technical guidance. The knowledge transfer method is carried out in the form of lectures and 2-way discussions as well as practice on how to hatch comet fish using semi-artificial hatchery techniques. Technical guidance receives appreciation and attention from members so it is hoped that partners can carry it out independently